Presbyopia-correcting performance and subjective outcomes of a trifocal intraocular lens in eyes with different axial lengths: A prospective cohort study - Tong Sun; Tong Sun; Yiyun Liu; Yiyun Liu; Xiaorui Zhao; Xiaorui Zhao; Yufei Gao; Tingting Yang; Tingting Yang; Qianqian Lan; Chuhao Tang; Chuhao Tang; et al. (Frontiers in Medicine, 2022)
PurposeTo compare the presbyopia-correcting performance, visual quality, satisfaction and life quality after implantation of a diffractive trifocal intraocular lens (IOL) in eyes with different axial lengths (AL).MethodsThis prospective cohort study enrolled patients with implantation of a trifocal IOL. Manifest refraction, uncorrected and distance-corrected visual acuity at different distances, contrast sensitivity, aberrations and IOL decentration were measured 3 months after surgery. Spectacle independence, adverse photic phenomena, overall satisfaction and life quality were assessed with a questionnaire.ResultsThis study included 61 eyes of 61 patients: 16 eyes in the short AL group, 28 eyes in the control group and 17 eyes in the long AL group. Postoperatively, the prediction error (PE) of spherical equivalent showed a difference (P = 0.002). The uncorrected near visual acuity in the long AL group was higher (P = 0.047). Although a higher IOL decentration was obtained in the long AL group (P = 0.034), no significant difference was found in contrast sensitivity and aberrations (all P > 0.05). In the questionnaire, patients in the long AL group showed a relatively lower spectacle independence at near distance (P = 0.060) and had difficulties in near activities, mental health and role in daily life (P = 0.003, 0.021, and 0.033). However, no significant difference was observed in overall satisfaction (P = 0.124).ConclusionWith detailed preoperative evaluation, the trifocal IOL provided satisfactory visual outcomes for patients with different AL. AL had a certain influence on predictability and IOL decentration. And for patients with long AL, the inadaptability to the near focal point might become an important problem.